Interpersonal communication and its implication in nursing - Barbara Pereira; Lara Freitas; Aline Gonçalves; Raul Santos; Sueli Vilela (Universidad de Alicante, 2019)
Introduction: Communication is a creative action, used to promote interaction, to understand social and psychological factors among individuals. It permeates human evolution. Objective: To search for studies that applied the interpersonal communication in the health area and to discuss how it is applied in the area of nursing. Method: This is a theoretical-reflexive study due to its characteristic of being problematizing, anti-dogmatic without, however, dispensing with logical-methodological rigor with coherence of argumentation and critical spirit. Barnlund's Theory of Transactional Communication was used as a reference. Result: Aiming to enable greater understanding and discussion, we chose to discuss interpersonal communication in three thematic categories: Barnlund Transactional Communication Theory, Characterizing Communication and Interpersonal Communication in Nursing. Conclusion: In nursing, the difficulty of interaction and communication between the professionals and the patients is also evidenced, a fact that proves that this difficulty compromises the integral attention to the individual, also compromising the quality of life of the same.